Experimental Verification of High-Resolution Wide-Swath Moving Target Indication - Baumgartner, Stefan V.; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2016)
Recently we have introduced a set of novel low pulse repetition frequency (PRF) algorithms, which allow for simultaneous high-resolution wide-swath (HRWS) SAR imaging and moving target indication (MTI) without the need of changing the system operation mode and the pulse repetition frequency (PRF). The core of these novel HRWS-MTI algorithms is the so called Matched Reconstruction Filter Bank (MRFB). By applying the MRFB, low PRF moving target signals can be reconstructed and refocused. Additionally, accurate estimates of the target motion parameters are obtained. In this paper the experimental verification of the MRFB principle is presented for the first time. For the verification real multi-channel airborne data acquired with DLR's F-SAR sensor over a maritime scenario are used.
DLR Import::2019-04-03